2022
DOI: 10.1186/s12934-022-01959-2
|View full text |Cite
|
Sign up to set email alerts
|

Designing synthetic consortia of Trichoderma strains that improve antagonistic activities against pathogens and cucumber seedling growth

Abstract: Background Trichoderma spp. are important agricultural biocontrol microorganisms that are often used as effective components of microbial fungicides and microbial biofertilizers. However, most of these products are prepared by a single strain in monoculture, which significantly limits the biocontrol efficiency and stability of Trichoderma products. Therefore, the establishment of a design and screening approach for consortia with multi-Trichoderma strains for co-culture is of great importance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…The role of T. asperellum as antagonistic against different plant fungi pathogens such as A. solani (Ronnie-Gakegne and Martínez-Coca, 2018), Fusarium oxysporum (Hao et al, 2022, Rubio-Tinajero et al, 2022Sharma et al, 2022), Sclerotinia sclerotiorum, A. solani, Phytophthora sphave (Sharma et al, 2022), Puccinia striiformis (Esmail et al, 2022) have been demonstrated. Alternaria comprise a group of species causing several damages on different plants, including apple trees, to which they can induce leaf blotch and fruit spot (Cabrefiga et al, 2023).…”
Section: Discussion Discussion Discussionmentioning
confidence: 99%
“…The role of T. asperellum as antagonistic against different plant fungi pathogens such as A. solani (Ronnie-Gakegne and Martínez-Coca, 2018), Fusarium oxysporum (Hao et al, 2022, Rubio-Tinajero et al, 2022Sharma et al, 2022), Sclerotinia sclerotiorum, A. solani, Phytophthora sphave (Sharma et al, 2022), Puccinia striiformis (Esmail et al, 2022) have been demonstrated. Alternaria comprise a group of species causing several damages on different plants, including apple trees, to which they can induce leaf blotch and fruit spot (Cabrefiga et al, 2023).…”
Section: Discussion Discussion Discussionmentioning
confidence: 99%
“…The growth-promoting abilities of different Trichoderma strains can vary. For example, in a study by [45], a cucumber growth-promoting experiment was conducted using 15 strains of Trichoderma. The results showed that strain T-10264 exhibited the most potent growth-promoting effect on cucumber seedlings in vitro.…”
Section: Discussionmentioning
confidence: 99%
“… Fusarium wilt in banana ( Fusarium oxysporum f. sp. cubense ) in vitro and greenhouse inhibiton of Fusarium , 100% reduction of Fusarium wilt disease, increase in plant growth parameters up to 250%, increase in IAA production and phosphate solubilisation Thangavelu and Gopi 2015 T. asperellum, T. harzianum and T. virens Ganoderma boninense in oil palm nursery trial reduction in foliar disease symptoms (by 83.03%) and bole damages (by 89.16%), increase in plant height and girth, dried shoot and root tissue weight Musa et al 2018 T. tomentosum and T. harzianum tryptophan supplementation in Zea mays microcosm increase in plant height, root length, leaf area, and dry weights in maize Herrera-Jiménez et al 2018 T. atroviride and T. citrinoviride Brassica chinensis growth promotion in vitro and greenhouse elevation of IAA and iron-chelating siderophore content, improved germination parameters and seedling growth Chen et al 2021 T. asperelloides, T. asperellum and T. harzianum Fusarium oxysporum , seed germination promotion in cucumber in vitro, artificial climate indoor cultivation, and field increase in amino acid and γ-aminobutyric acid levels, increased plant height and stem diameter Hao et al 2022 Two T. asperellum isolates Fusarium root and stem rot in cucumber plants (Fusarium oxysporum f. sp. radices-cucumerinum) greenhouse reduction in reactive oxygen species accumulation and activation of antioxidant enzymes, strong mycoparasitic effect in the case of application of multiple Trichoderma strains El-Komy et al 2022 T. viride and T. harzianum Fusarium oxysporum in cherry tomatoes ...…”
Section: Multicomponent Inoculants Containing Trichodermamentioning
confidence: 99%